Values-Based Organizational Culture and Employee Engagement: Pathways to Sustainable Organizational Performance - Varias, Vina; Akbar, Muhammad Aliyandri; Risa, Tiara Dean; Bhirawa, Madyastha Aji; Nugraha, Risman (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines the relationship between values-based organizational culture and employee engagement in fostering sustainable organizational performance through a qualitative library research approach. In the context of increasing organizational challenges such as employee disengagement, ethical deterioration, and sustainability pressures, organizations are required to adopt human-centered and value-oriented management strategies. Prior studies often address organizational culture, employee engagement, and sustainability as separate constructs, resulting in fragmented theoretical understanding. Using a qualitative library research design, this study systematically reviews and synthesizes relevant literature from Scopus-indexed journals, books, and authoritative academic sources in the fields of industrial–organizational psychology, organizational behavior, and sustainability studies. A thematic analysis was conducted to identify recurring concepts and theoretical linkages among values-based culture, psychological engagement, and sustainable performance. The findings reveal five core themes: (1) values-based organizational culture as a moral and psychological foundation, (2) employee engagement as a multidimensional psychological mechanism, (3) meaningful work and value alignment as drivers of sustained engagement, (4) sustainable organizational performance beyond financial outcomes, and (5) the need for an integrative conceptual framework. The study highlights that organizational values play a strategic role in shaping employees’ emotional and cognitive attachment, which in turn supports long-term adaptability, ethical consistency, and organizational resilience. This research contributes theoretically by offering an integrative conceptual model that positions employee engagement as a mediating mechanism between values-based culture and sustainable performance. Practically, the study provides insights for organizations seeking to embed ethical values and engagement-oriented practices as foundations for sustainable development.